1982
DOI: 10.1159/000468562
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Neurotoxicity in Schizophrenie and Schizoaffective Patients

Abstract: A large variability in the rates of lithium-induced toxic-confusional states is noted in studies of lithium treatment of schizophrenic and schizoaffective patients. Treatment and subject factors which might contribute to this variability are reviewed. A greater frequency of lithium-induced toxic-confusional states is found in more acutely ill schizophrenic and schizoaffective patients. The possibility that some behavioral states may increase the risk for lithium neurotoxicity is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, West identified journal articles and reviewed the evidence on lithium neurotoxicity in patients with schizophrenia and schizoaffective disorder. 11 He made mention of three researchers who reported varying frequencies of a lithium-induced confusional state: Johnson found it very common (>10% of n = 7), Prien found it common (1-10% of n = 36), and Zall found it rare (<0.01% of n =10) for patients treated with lithium to experience such a state. 12,13,14 Additional studies attempted to explain the mechanism of a lithium-induced confusional state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, West identified journal articles and reviewed the evidence on lithium neurotoxicity in patients with schizophrenia and schizoaffective disorder. 11 He made mention of three researchers who reported varying frequencies of a lithium-induced confusional state: Johnson found it very common (>10% of n = 7), Prien found it common (1-10% of n = 36), and Zall found it rare (<0.01% of n =10) for patients treated with lithium to experience such a state. 12,13,14 Additional studies attempted to explain the mechanism of a lithium-induced confusional state.…”
Section: Resultsmentioning
confidence: 99%
“…In a 1982 literature review, West reported variations in the frequency of a lithium-induced confusional state in patient. 11 He attributed these variations to individual differences in absorption and excretion of lithium, and acute exacerbations of illness. However, other patient characteristics (i.e., sex, age, and concomitant medical illnesses and medications) must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Various hypotheses have been proposed to explain this phenomenon; for instance, ECT may increase the permeability of the blood-brain barrier (BBB), thereby increasing cerebral blood flow [ 22 ]. This dysfunction may cause a sudden increase in lithium ions entering the brain or a redistribution of concentrations within cerebral tissue compartments, resulting in peak levels observed in white matter [ 23 ]. Age-related factors can influence BBB permeability fluctuations as well as chemical means [ 24 ] in human subjects.…”
Section: Discussionmentioning
confidence: 99%